World(s) - Gržinić, Marina (Filozofski vestnik, 2022)
The main thesis of this text is that for a critical evaluation of the institutions built on the foundations of colonialism that preserve the worlds of neoliberal global capitalism, financial capitalism, and necro-capitalism, we need to rethink the two main divisions mediated by decolonial theory and decolonisation as analytical tools: the racial/colonial divide and the imperial/colonial divide. This text attempts to analyse the relation between capitalism and colonialism in order to determine the implications for the theoretical and philosophical thought of two historical forms of capitalism, which are not historical at all because they are fully functional in the present: racial capitalism and settler capitalism, or racial-settler capitalism, as it is called in its joint formation. In order to get to this point, we must first see the place of colonialism in capitalism and how theory is reflected in its relationship to the past and present. Last but not least, the question this article is occupied with is: “What kind of world is this where a trans person, a woman, or a man is treated like garbage?”